A Case study on fresh interior design graduates' transformed domestic spaces into WFH-friendly spaces - Lagman, Nadine Louise C. (College of Home Economics, University of the Philippines Diliman, 2021)
This study has been conducted in order to provide a glimpse of the new normal in the design field of work and attempted to determine and analyze how selected Interior Designers have adapted and transformed their existing domestic spaces to functional work spaces during the pandemic. The purpose of this study were to describe the existing Work-From-Home (WFH) settings that selected Interior Designers have done in their domestic interiors, identify the design strategies applied by the respondents in setting up their WFH work stations, and analyze how the respondents addressed the requirements for an efficient WFH work stations in their domestic interiors. A qualitative research approach was used for this study and purposive sampling was done to assure that the study was strictly conducted among fresh interior design graduates only. The data were gathered through online survey forms, photo documentation, and online interviews. The collected data were listed and tabulated to discover similarities and prevalent themes in the transformation of their home-offices. The application of Kaplan's Art Restoration Theory and Hall's Proxemics were explored to determine how the participants transformed their new home-offices. Location of the workspace, tasks, and work habits and strategies were analyzed to understand their considerations in the spatial environment. Results showed that the interior designers prioritized privacy, efficiency and availability as the main factors they considered along with the work habits that greatly influenced the transformation done in the space. This study found out that there are mainly three considerations - comfort, functionality, and budgetary reasons - that influenced the transformation of their existing domestic spaces into WFH-friendly enviromments.